RAV14N2, Message from the Editor in Chief (May – August 2024) - Castro Borges, Pedro (Revista ALCONPAT, 2024)
JOURNAL OF THE LATIN AMERICAN ASSOCIATION OF QUALITY CONTROL, PATHOLOGY AND RECOVERY OF CONSTRUCTIONhttp://www.revistaalconpat.org It is a source of satisfaction and joy for the ALCONPAT Journal team to see the second issue of our fourteenth year published.The objective of ALCONPAT Journal (RA) is the publication of citable production (basic or applied research, and reviews), documentary research and case studies, related to the themes of our association, that is, quality control, pathology and recovery of the constructions.This V14 N2 edition begins with a work from Mexico, where José Manuel Mendoza Rangel and colleagues review the 3D printing of cementitious materials (I3DMC) evaluating their suitability to build Decent, Affordable and Sustainable Housing (ViDAS) in Mexico, considering the mechanical requirements, for durability and sustainability. The climate and economic crisis are current challenges for a Circular Construction Industry, but I3DMC reduces CO2 emissions, materials and waste, labor, times and costs by up to 88%, 50%, 70% and 90%, respectively, achieving the resistance and durability of conventional construction. Likewise, there are I3DMC companies in developed countries, but importing this technology to developing countries is not affordable, therefore, research into I3DMC technologies is ongoing in Nuevo León, Mexico, allowing the construction of ViDAS for $1,700-$4,500/ m2.In the second work, from Mexico, Irma Elizabeth Betancourt-Castillo and Oswaldo Burciaga-Díaz investigate the effects of alkaline activation with MgO-NaOH on the compressive strength and reaction products of cements alkaline activated with stone powder limestone (PClz) and Class C fly ash (CV). The results showed that the substitutions of 25% < PCIz < 75% allowed 25-76 MPa at 360 days of curing, obtaining the highest resistance with 25%PClz-75%CV and 50%PClz-50%CV with 10 and 12 % NaOH-MgO respectively. The results suggest that PCLz participates in hydration reactions as a filling and nucleating agent while CV is the main contributor to the progression of chemical reactions. X-ray diffraction (XRD), thermal analysis (TA) and scanning electron microscopy (SEM) indicated the formation of M-S-H and C, N-A-S-H type products, in addition to carbonate phases such as hydrotalcite, gaylussite and pirssonite. No traces of unreacted MgO were observed, indicating its complete incorporation into the reaction products.The third work in this issue is from Mexico, where Jorge Varela-Rivera and colleagues present a study on the shear behavior of confined masonry walls made of autoclave cellular concrete (CCA). Five reduced-scale CCA confined walls were tested subject to lateral loads. The variables studied were the geometric scale factor and the aspect ratio of the walls. Scales 1:2 and 1:3 were considered. Based on the behavior of the walls at a reduced and natural scale, experimental scale factors were determined. The existing geometric scaling factors were compared with the corresponding experimental ones. It is concluded that the geometric scale factors can be used to predict the shear resistance and maximum shear resistance of walls with scales 1:2 and 1:3. Geometric scaling factors can only be used to predict the stiffness and distortion associated with ultimate shear strength.In the fourth article, Jorge Humberto Chávez-Gómez and colleagues from Mexico use a Digital Image Correlation (DIC) technique to analyze displacements in masonry walls subjected to axial compression, without using a commercial program. An algorithm was developed using the Newton Raphson numerical method for this purpose. The results obtained were compared with the measurements of the linear variable differential transducer (LVDT), validating the effectiveness of the algorithm and comparing them with previous studies, with acceptable errors. This work is part of an ongoing project at the Institute of Civil Engineering of the Autonomous University of Nuevo León, establishing the bases for future research on the implementation of the technique to obtain pathologies and deformational states in masonry structures. The main conclusion was that the DIC could be used as a reliable measurement method for displacements and deformations in laboratory tests.The fifth article, by Carlos Alberto Torres Montes de Oca, José Eduardo Rosas Valencia and Oswaldo Aldair Pérez Jarquín, comes from Mexico. They investigate how to denote the application of numerical-vector succession in the structural analysis of historic masonry buildings, with arches and symmetrical systems, including mathematical processes in ancient graphic analysis, emphasizing the importance of loads in structural stability. The analyzes are based on three fundamental stages: recognition of the construction system of the heritage object, geometric discretization of the system and vector analysis under different physical considerations. Thus, the thrust lines are affected by the loads, the boundary conditions and the history of the structural behavior of the heritage object. Numerical and computational tools offer faster and more precise graphic analysis processes. The authors conclude that these methods provide very particular results and some of them are similar, so it is recommended to use the methods as a complement and not classify one over the other.The article that closes the edition is by José Levi Chaves de Sousa and Carlos Ochoa from Brazil, who analyze whether there are differences in the classification of the surface condition of a flexible road pavement using Continuous Visual Survey (CLV) and the Global Severity Index (IGG). A segment of road covered with Asphalt Concrete was selected, with the objective of evaluating the costs associated with each classification. Due to the limitation of a longer time to obtain the IGG, the analysis was limited to that segment. The results revealed divergences in the classifications and costs of the methods in the initial road segments. It was concluded that the LVC offered better results than the IGG, attributable to the inherent subjectivity of human evaluation. Furthermore, it was observed that the two methods complement each other in the functional analysis of road pavements.We are confident that the articles in this issue will constitute an important reference for those readers involved with issues of evaluations and characterizations of materials, elements and structures. We thank the authors participating in this issue for their willingness and effort to present quality articles and meet the established deadlines.At the close of this V14 N2 2024, 14 years after starting operations, our performance as Alconpat Journal was finally rewarded with our inclusion in one of the two best indexes for journals such as Elsevier's Scopus. We already have a modest impact factor (0.3), which I am sure will increase thanks to you, our readers, and the quality of our articles. Our membership in Scopus has its historic beginning on December 29, 2022, the date on which we received approval from Elsevier. We hope during 2024 to apply to Journal Citation Reports, which is the index with the greatest international coverage and quality. These are reasons to celebrate for our community that has made a scientific investment in our journal waiting for moments like this. Congratulations to all.On behalf of the Editorial Board Pedro Castro Borges          Editor in Chief